(untitled) (Journal of Engineering, 2005)
This paper studies the non-linear behaviour of a clayey Iraqi soil taken from Baghdad City, using the bounding surface plasticity model under static and dynamic loading. The bounding surface plasticity model needs a group of input parameters. Some of them are determined directly from triaxial and consolidation tests, while the others are evaluated from a parametric study using a computer program named EVAL.A series of advanced laboratory tests was performed after modifying and manufacturing some parts of the triaxial machine that are required for carrying out Ko-consolidtated compression and extension tests. The soil test results are used in a computer program named EVAL to compute the soil properties and input parameters for the Iraqi clayey soil under consideration that are required in the bounding surface plasticity model. After the input parameters became available, one could use them in finite element computer programs for static and dynamic analyses. Two-finite element programs are chosen. The first program, named ACED used for solving coupled problems under static loading. While the second program, named LEARN, is used for solving dynamic problem. The proposed abbreviation of Baghdad silty clay soil is (BBSC)..